Collaborare online per la progettazione educativa. Un ambiente web di scrittura collaborativa come laboratorio nella formazione universitaria - Pillera, Giuseppe (Studi sulla Formazione/Open Journal of Education, 2015)
How can we support group collaboration about designing human and social change? This paper reports three years of blending laboratory at university course about pedagogic models for educational planning and it especially explores about methodology, tools, participants, activities and assessment, with regard to group-based collaborative writing set in a specially made web environment.